2019
DOI: 10.1121/1.5132710
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of acute hearing changes in United States military populations

Abstract: Until recently, most hearing conservation programs, including those in the military, have used permanent shifts in the pure-tone audiometric threshold as the gold standard for measuring hearing impairment in noise-exposed populations. However, recent results from animal studies suggest that high-level noise exposures can cause the permanent destruction of synapses between the inner hair cells and auditory nerve fibers, even in cases where pure-tone audiometric thresholds eventually return to their normal pre-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
9
0
2
Order By: Relevance
“…Nonetheless, such results do not assure that protection will extend to more robust noise exposure with greater injury to the cochlea. The limited availability of clinical trial populations in which otoprotection can be investigated has been discussed in several recent reports (56,102) (19,20,163). The vast majority of the studies identified here used the audiogram as the primary outcome.…”
Section: Tinnitusmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, such results do not assure that protection will extend to more robust noise exposure with greater injury to the cochlea. The limited availability of clinical trial populations in which otoprotection can be investigated has been discussed in several recent reports (56,102) (19,20,163). The vast majority of the studies identified here used the audiogram as the primary outcome.…”
Section: Tinnitusmentioning
confidence: 99%
“…Of the PTS prevention trials summarized in Tables 1 (pre-treatment) and 2 (posttreatment), five included soldiers exposed to weapons fire (7,18,27,68,83,197), one included safety officers exposed to weapons fire (NCT04774250), one included impulse noise produced by firecrackers (173), and one included patients exposed to drilling noise While not the only source of noise exposure for soldiers, the hazards of auditory injury as a consequence of military weapon sound are well known (71), and the problem of NIHL in service members is significant (41,56,177,196). Dangerously high sounds levels are well documented during discharge of semi-automatic rifles (see for example 115,120).…”
Section: Tinnitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Los procedimientos y evaluaciones de las afectaciones del ruido en los combatientes han evolucionado y perfeccionado con el tiempo, buscando ser más precisos y cercanos a la realidad, como lo constituye la propuesta de caracterización de enfermedades agudas adquiridas a corto plazo por parte de la población militar (Hecht et al, 2019), la cual promueve la realización de pruebas audiométricas antes e inmediatamente después de la exposición a ruidos continuos, como los generados por buques, tanques, ruidos impulsivos como los de un rifle o explosiones que pueden alcanzar los 180 dB. La aplicación de estos test no es del todo factible, debido a los altos costos, ya que la audiometría debe realizarse en exteriores y en condiciones totalmente diferentes a las convencionales.…”
Section: Cross-sectional Study: Noise-induced Hearing Loss In Ecuadorian Military Aviation Personnelunclassified
“…En el caso de ejercicios en el terreno por ejemplo, las prácticas con explosivos superan los 175 dB (Hecht, Hammill, Calamia, Smalt, & Brungart, 2019), comparable con el ruido percibido en los portaviones (Yankaskas, Hammill, Packer, & Zuo, 2017). Así mismo, se conoce que ciertas labores repetitivas en el campo de la aeronáutica, han producido importantes niveles de hipoacusia en el personal de pilotos, técnicos e ingenieros de vuelo (Carpio & Álvarez, 2017).…”
Section: Introductionunclassified